Embryonic development of the Drosophila brain: Formation of commissural and descending pathways. - Therianos, S.; Leuzinger, S.; Hirth, F.; Goodman, C.S.; Reichert, H. (Development, 1995)
The establishment of initial axonal pathways in the embryonic brain of Drosophila melanogaster was investigated at the cellular and molecular level using antibody probes, enhancer detector strains and axonal pathfinding mutants. During embryogenesis, two bilaterally symmetrical cephalic neurogenic regions form, which are initially separated from each other and from the ventral nerve cord. The brain commissure that interconnects the two brain hemispheres is pioneered by axons that project towards the midline in close association with an interhemispheric cellular bridge. The descending longitudinal pathways that interconnect the brain to the ventral nerve cord are prefigured by a chain of longitudinal glial cells and a cellular bridge between brain and subesophageal ganglion; pioneering descending and ascending neurons grow in close association with these structures. The formation of the embryonic commissural and longitudinal pathways is dependent on cells of the CNS midline. Mutations in the commissureless gene, which affects growth cone guidance towards the midline, result in a marked reduction of the brain commissure. Mutations in the single-minded gene and in other spitz group genes, which affect the differentiation of CNS midline cells, result in the absence or aberrant projection of longitudinal pathways. The analysis of axon pathway formation presented here reveals remarkable similarities as well as distinct differences in the embryonic development of the brain and the segmental ganglia, and forms the basis for a comprehensive genetic and molecular genetic dissection of axonal pathfinding processes in the developing brain.